MAIZE SEED VIGOR AND ITS EFFECTS ON CROP CULTIVATION CYCLE - Mondo, Vitor Henrique Vaz; Dias, Marcos Altomani Neves; Cicero, Silvio Moure (REVISTA DE AGRICULTURA, 2015)
Seed vigor usually does not interfere in grain yields when crop is harvested at maturity, however, on crops harvested at vegetative stages, its effects are noticed. Therefore, this study aimed to investigate influences of maize seed vigor on crop cycle. Four maize seed lots differing on seed vigor were planted in the field and daily evaluated, computing growing-degree-days for each plot to reach each phenological stage. It was observed plant development differences among treatments, which occurred at emergence, 4th, 8th and 12th fully expanded leaves and at milk stage. Therewith, it is possible to affirm that seed vigor has impacts on crop cultivation cycle, with plants from low vigor seeds presenting a delayed development. However, those differences tend to disappear during the reproductive phase.